2008
DOI: 10.1093/jnci/djn415
|View full text |Cite
|
Sign up to set email alerts
|

Insulin, Insulin-Like Growth Factor-I, and Risk of Breast Cancer in Postmenopausal Women

Abstract: These data suggest that hyperinsulinemia is an independent risk factor for breast cancer and may have a substantial role in explaining the obesity-breast cancer relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
387
6
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(425 citation statements)
references
References 49 publications
22
387
6
10
Order By: Relevance
“…Table 2 The mean, median/interquartile range (IQR) , and hazard ratio for recurrence for insulin, IGF-binding protein-1 (IGFBP-1) Evidence from the European Prospective Investigation into Cancer and Nutrition (EPIC) suggested a positive association between IGF and breast cancer incidence only among postmenopausal women (Rinaldi et al 2006), while previous study findings suggested an association only among premenopausal women (Renehan et al 2004). More recently, a pooled analyses of 17 prospective studies found a positive association between IGF1 and breast cancer incidence regardless of menopausal status (Endogenous Hormones and Breast Cancer Collaborative Group 2010), while results from the Women's Health Initiative Cohort and the Japan Collaborative Cohort Study for Evaluation of Cancer Risk failed to find an association (Gunter et al 2009, Sakauchi et al 2009). The study by Goodwin et al (2002), one of the few prospective studies that investigated the association of IGF1 and insulin in relation to breast cancer recurrence, reported comparable results and found a non-significant HR for recurrence of breast cancer among women with the highest IGF1 quartile compared with the lowest quartile (1.55 (95% CI 0.93-2.59)).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Table 2 The mean, median/interquartile range (IQR) , and hazard ratio for recurrence for insulin, IGF-binding protein-1 (IGFBP-1) Evidence from the European Prospective Investigation into Cancer and Nutrition (EPIC) suggested a positive association between IGF and breast cancer incidence only among postmenopausal women (Rinaldi et al 2006), while previous study findings suggested an association only among premenopausal women (Renehan et al 2004). More recently, a pooled analyses of 17 prospective studies found a positive association between IGF1 and breast cancer incidence regardless of menopausal status (Endogenous Hormones and Breast Cancer Collaborative Group 2010), while results from the Women's Health Initiative Cohort and the Japan Collaborative Cohort Study for Evaluation of Cancer Risk failed to find an association (Gunter et al 2009, Sakauchi et al 2009). The study by Goodwin et al (2002), one of the few prospective studies that investigated the association of IGF1 and insulin in relation to breast cancer recurrence, reported comparable results and found a non-significant HR for recurrence of breast cancer among women with the highest IGF1 quartile compared with the lowest quartile (1.55 (95% CI 0.93-2.59)).…”
Section: Discussionmentioning
confidence: 94%
“…Most studies on IGF1 and its binding proteins have investigated their associations with breast cancer incidence rather than recurrence (Kaaks et al 2002, Renehan et al 2004, Rinaldi et al 2006, Gunter et al 2009, Sakauchi et al 2009, Endogenous Hormones and Breast Cancer Collaborative Group 2010). Table 2 The mean, median/interquartile range (IQR) , and hazard ratio for recurrence for insulin, IGF-binding protein-1 (IGFBP-1) Evidence from the European Prospective Investigation into Cancer and Nutrition (EPIC) suggested a positive association between IGF and breast cancer incidence only among postmenopausal women (Rinaldi et al 2006), while previous study findings suggested an association only among premenopausal women (Renehan et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia adversely affects prognosis in cancer patients (3,(7)(8)(9)(10)(11) and is an independent risk factor for several types of neoplasms, thus explaining the obesity-cancer association (12). Insulin can promote tumorigenesis through a direct effect on epithelial tissues acting on the insulin/insulin-like growth factor family of receptors (13), or indirectly by affecting the levels of other modulators, such as insulin-like growth factors, sex hormones, and adipokines (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of diets of high GI is linked with high blood glucose and insulin levels (Dong and Qin, 2011). Both substances have been positively associated with breast cancer (Larsson et al, 2007;Tworoger et al, 2007;Gunter et al, 2009;Minatoya et al, 2013). There was evidence that plasma C-peptide is increased at high insulin concentrations, and the marker is directly linked with GL (Wu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%